IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SDN 10 WAY SERDANG - Rian Wigi; Jaenullah; Ihsan Mustofa (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2024)
Implementing the Project Based Learning learning model is the right way and can be a solution in overcoming problems with student learning outcomes in Islamic Religious Education subjects. This research uses a qualitative descriptive approach method. The results of implementing Project Based Learning show an increase in scores to between 70 and 82, above the Minimum Completion Criteria (KKM), namely 9 students or 75% of all students, and the results of the summative evaluation of students show an increase in scores, namely between 70 and 76, exceeding the Completion Criteria scores. Minimum (KKM) or there are 9 students or 75% of the total number of students. From the results of this research, it can be concluded that student learning outcomes in implementing the Project Based Learning learning model in Islamic Religious Education lessons in class 5 of the 10 Way Serdang State Elementary School have increased quite significantly, which is reflected in student learning outcomes before using the Project Based Learning learning model. The conclusion in this research is that the implementation of the Project Based Learning learning model significantly influences the learning outcomes of Islamic Religious Education.